Continuing Professional Development for ECCE Teachers in Selected States in Malaysia: What Teachers and Operators Say - Dhamotharan, Dr Mogana Dhamotharan; Vijayan, Priya; Loh, C. (Advances in Social Sciences Research Journal, 2019)
Continuing professional development (CPD) is accepted as an integral part of teacher education because only continuing learning and training assures a high level of expertise and enables the teachers to keep their professional skills and knowledge up-to-date. CPD therefore should not be regarded only as an obligatory activity just to meet the required training hours set by supervisors, operators and educational settings. This paper primarily aims to present the preliminary findings of early childhood teachers’ and operators’ needs and concerns for continuing professional development for Early Childhood Care and Education teachers in selected states of Malaysia.